Zeolite Imidazole Framework-ZIF-8: Synthesis and Voltammetric Determination of Lead Ion Using Modified Electrode Based on ZIF-8 - Phong, Nguyen Hai; Thanh, Mai Thi; Tien, Duong Cat; Tinh, Mai Xuan; Hung, Nguyen Phi; Khieu, Dinh Quang (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Zeolite Imidazole Framework (ZIF-8) composite was prepared and used as a novel electrode modified for the determination of trace levels of lead. ZIF-8 shows quite a good capability for the efficient adsorption of lead from aqueous solutions. The parameters affecting the electrochemical process, such as types of electrodes, solvents, the amount of ZIF-8 suspension, electrolytic solution pH of were investigated. Under the optimal conditions, the electrochemical sensor exhibited a linear response to the concentration of lead in the range of 2-500 ppb with a detection limit of 8.6 ppb. The RSD is 6.88% and 6.93% at concentration of 5 ppb and 20 ppb, respectively. Keywords: Zeolite Imidazole Framework (ZIF-8); Modified electrode; Differential  Pulse  Anodic  Stripping Voltammetry; Bismuth  ﬁlm (BiF); Determination of Pb(II).